(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2021)
In this research a numerical simulation of the micro-jet system used to cool an electronic chip was performed, as it was of type multijet, the basic idea of how the impingement cooling method works on the micro jet cooling array was provided by these simulations that consisted of a variety of parameters: Reynolds number (500-3000), diameter of jets (150-750) µm, number of jets (11,13,15,19,21), and distance between jets and target (450,337.5,225,168.75,112.5) µm. Shear stress transport (SST) K-? model was used because it’s able to predict the laminar to turbulent transition according to previous research. The input heat flux =36421 w/m² and area of plat (28700×28700) µm². The result shows the performance was improved when the jet diameter was increased, as the highest value of the Nu was obtained at (d = 600µm) and the losses were reduced. Also, the performance improved when the number of jets was increased.